How to start a blog. Issue 3 (12th April 2017) - Thomson, Alison; Raciborska, Dominika; Baker, David; Giovannoni, Gavin
Abstract : Blogs that address issues of health and medical education run by clinical and research teams can have a profound impact on how patients access and navigate health information. Regularly updated websites are useful tools to facilitate two-way communication with a range of different audiences from patients to the general public. They provide benefits of supporting patients to learn and self-manage their health, and to educate colleagues and disseminate research. This article describes how to set up a blog, pointing out some simple style and formatting considerations, usable methods and appropriate conduct for healthcare professionals to engage with patients online.